Optimization of Group Discussion Method to Increase Active Student Involvement in Islamic Education Learning at SD Negeri No. 107967 Pelintahan - Kodar, Arbainur; Hilaiyah (Jurnal Profesi Guru Indonesia, 2024)
This study aims to optimize the group discussion method in learning the history of the Prophet Muhammad SAW in order to increase the active involvement of students in grade V of SD Negeri No. 107967 Pelintahan. The history of the Prophet Muhammad SAW is a very important material in Islamic religious education at the elementary school level, but is often considered difficult to understand by students. Therefore, a learning approach is needed that can facilitate student understanding in a more interactive and interesting way. The group discussion method was chosen as a solution to increase student involvement, because in this method students can exchange ideas, collaborate, and be actively involved in the learning process. This study uses a quantitative approach with an experimental design, where students are divided into groups to discuss topics on the history of the Prophet Muhammad SAW, then their involvement is measured through observation, questionnaires, and assessment of the results of the discussion. The results showed that the group discussion method significantly increased student participation, with many students actively asking questions, discussing, and showing a better understanding of the material. In addition, the results of the final test showed an increase in student understanding of the history of the Prophet Muhammad SAW. Based on these findings, it is recommended that the group discussion method be applied more widely in history learning in elementary schools to effectively increase student involvement and understanding.